2017
DOI: 10.4314/acsj.v25i1.8s
|View full text |Cite
|
Sign up to set email alerts
|

Collective market participation for improved income among smallholder farming households: a case of Balaka Innovation Platform in Malawi

Abstract: Collective market participation can reduce transaction costs and information asymmetries, which can build up market power. The objective of this study was to evaluate decisions to participate in collective marketing and its effect on household income among smallholder farmers in an Innovation Platform (IP). This study targeted the Balaka IP in Malawi. Collective marketing identified as critical for improving households' incomes, is one of the activities that Balaka Innovation Platform has been addressing since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
(25 reference statements)
7
14
0
Order By: Relevance
“…The finding was consistent with similar findings of most of earlier studies which found age to be positively correlated to likelihood of group participation. According to [13,16,29,30], majority of younger population preferred to look for other sources of employment than engage in agricultural activities. From the result, it is clear that young people especially the male are yet to embrace agribusiness, or engage in agricultural activities as source of livelihood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The finding was consistent with similar findings of most of earlier studies which found age to be positively correlated to likelihood of group participation. According to [13,16,29,30], majority of younger population preferred to look for other sources of employment than engage in agricultural activities. From the result, it is clear that young people especially the male are yet to embrace agribusiness, or engage in agricultural activities as source of livelihood.…”
Section: Discussionmentioning
confidence: 99%
“…This is plausible because a farmer who owns a mobile phone can access information easily regarding scheduled meetings. According to [13,30], banana producers who own mobile phones are easy to be contacted and given information regarding group formation, and notification about group meetings. Finally, access to extension advice increased the probability of collective action participation by a household at 1% significant level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the studies investigating the contribution of MSPs to intervention performance are partial in terms of their coverage and methods. Quantitative studies have compared pre-and post-intervention data (Pamuk et al, 2014) and demonstrated both positive and negative contributions (Martey et al, 2014;Pamuk et al, 2014;Mango et al, 2017). However, they do not report on specific factors that contributed to that proclaimed positive or negative influence.…”
Section: General Introductionmentioning
confidence: 99%